A PARTIAL LEAST SQUARE MODELLING FOR ANALYSIS THE IMPACT OF WELFARE TO ENTREPRENEURSHIP CLIMATE IN OECD COUNTRIES - Ufuk Bingöl (Akademik İncelemeler Dergisi)
Socio-economic issues in countries all over the world affect the entrepreneurship ecosystem. The impact of socio-economic issues and developments on individuals' lives conceptualizes welfare. In this sense, the relationship between the welfare of the countries and the entrepreneurial climate is the object of interest. This study aims to investigate the impact of socio-economic welfare on entrepreneurial climate in OECD countries with the PLS-SEM method by using OECD's Better Life Index and Worldbank Ease of Doing Business Index for 2020. This study contributes to previous literature by reversing the analysis of the relationships between entrepreneurship and well-being. The model established with the assumption that all sub-indicators of the better life index positively impact the ease of doing business, only correlated with income, employment, and education indicators. However, there is only a positive and significant relationship between the education variable and ease of doing business at p <,001 level among these correlations. According to results, the duration in education, education level of the working-age population, and the increase in the PISA averages of the countries increase the ease of doing business in terms of entrepreneurship climate